THU0010 The Significance of Ectopic Germinal Center in Minor Salivary Gland of Patients with SjÖGren's Syndrome. (10th June 2014) - Lee, K.-E.; Lee, S.-S.; Park, D.-J.; Lee, J.-W.; Kang, J.H.; Wen, L.; Kim, T.-J.
Abstract : Objectives: To investigate whether the presence of germinal center (GC) in minor salivary glands of patients with Sjögren's syndrome (SS) is associated with different clinical and laboratory features. Methods: Minor salivary gland tissue biopsies from 93 SS patients were used to identify GC-like structures and germinal center was confirmed by CD21-positive follicular dendritic cell networks. Sociodemographic, glandular, and extraglandular manifestations, and laboratory findings including autoantibodies, complement, and immunoglobulin levels, were analyzed. EULAR SS disease activity index (ESSDAI) and SS disease damage index (SSDDI) were also measured. Results: GC-like structures were observed in 28 of 93 SS patients (30.1%). Mean focus score was significantly higher in GC-positive patients than in GC-negative patients. GC-positive patients had higher CRP levels and had higher prevalence of rheumatoid factor, anti-CCP antibody, and anti-SSA/Ro antibody compared to GC-negative patients. However, glandular and extra-glandular manifestations were not different between the two groups. Conclusions: Our findings showed that SS patients who had GC-like structures in minor salivary glands had different laboratory profiles compared to those patients who didn't have. Long-term follow-up of these patients will be necessary to see whether these laboratory abnormalities translate into changes in clinical features. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2681